Northern Ireland's elusive peace dividend: Neoliberalism, austerity and the politics of class. (March 2019) - Coulter, Colin
The signing of the Good Friday Agreement was meant to signal an era of economic prosperity for those working-class communities that suffered most during the Troubles. Two decades on, this much vaunted 'peace dividend' has yet to materialise. A combination of persistent economic stagnation and the onset of austerity has ensured that the poverty and inequality that marked the era of political conflict continue to blight Northern Irish society. The introduction of the 2012 Welfare Reform Act momentarily created the conditions of the possibility of a more progressive politics premised on issues of social class. The decision of the United Kingdom to leave the European Union would, however, close down this nascent political space and ensure the resurgence in Northern Irish public debate of those ethno-national preoccupations that animate the 'constitutional question'.